Assessment of Some Immunological Parameters Postvaccination with Different Types of COVID-19 Vaccines - Haneen Saad Khasbak; Hayder Shkhair Al-Janabi; Mohanad Jawad Kadhim (Medical Journal of Babylon, 2025)
Background: Coronavirus disease 2019 (COVID-19) is a highly contagious viral infection that can spread rapidly worldwide. Several vaccines have been developed to combat COVID-19. Objectives: This study aimed to assess some immunological parameters, including CD8+ and IgG levels in sera of different vaccinated groups with different types of COVID-19 vaccines. Materials and Methods: The current study included 75 samples from vaccinated persons with AstraZeneca, Sinopharm, and Pfizer vaccines and 25 unvaccinated (naturally infected) persons. CD8+ and IgG levels were measured using ELISA technique. Results: The results showed that the CD8+ level increased significantly (P < 0.05) in the Pfizer vaccinated group than in Sinopharm and AstraZeneca groups, and there were no significant differences in the CD8⁺ level in the Pfizer-vaccinated group and unvaccinated group. The results also showed significant differences between CD8+ levels in males (22.78 ± 3.36) and females (9.86 ± 1.16) in Sinopharm vaccine, whereas there were no significant differences in CD8+ levels between males and females in other vaccine groups. COVID-19 IgG antibody levels were elevated significantly in unvaccinated people compared to those who received the Pfizer vaccine. In contrast, there were no significant differences in concentration of IgG antibodies between Sinopharm, AstraZeneca vaccines, and unvaccinated groups. Notably, the Pfizer vaccine exhibited significantly lower IgG levels in all age groups compared to the other vaccines. Conclusion: The Pfizer vaccine induced a cellular immune response represented by CD8+ levels than other COVID-19 vaccines and unvaccinated (naturally infected) people, while natural immunization had higher IgG by inducing a humoral immune response than COVID-19 vaccines.